Correlation of Igneous Rock Characteristics in Mount Mujil and areas Based on the Petrological Approach of Volcanic Rocks - Novaldi Yahya Arif Guntara (ReTII, 2021)
The location of research is located at east part of Kulonprogo mountains, exactly on Mujil mountain which are composed by the Formation of Kebobutak (Tmok). Its appearance is in the form of an isolated hill among surroundings, making different interpretations of experts regarding the genetic of Mujil mountain, and make the geological conditions in the research area interesting enough to be studied, especially the characteristics of the igneous rocks. This research is intended to completing existing geological data, so it can be used as complementary data in the interpretation of the Mujil mountain genetic. The research methods used surface data acquisition continued by petrological analysis and petrographic. The result of analysis from the 9 observation locations, it was concluded that the rocks is varied between the Basaltic Andesite to Pyroxene Andesite (Streckeisen, 1978). Based on the data, here are anomalies in LP-1 and LP-9 which are more basaltic than others so that it is interpreted as a product of volcanism that is different from the surroundings both in the form of volcanic products (monogenetic system) or the result of the stepped down of volcanic products around it.